Cerebrospinal fluid sex steroid hormones in bacterial meningitis. Issue 36 (9th September 2022) - Dias, Sara P.; Brouwer, Matthijs C.; Boelen, Anita; van de Beek, Diederik
Abstract : Unfavorable outcome in bacterial meningitis is related to excessive inflammation and higher inflammatory markers have been reported in female than in male patients. Sex steroid hormones have immunomodulatory properties and can be found in the cerebrospinal fluid (CSF); however, their actions have not been studied in bacterial meningitis. We investigated the association between CSF sex steroid hormone levels and inflammatory parameters, disease severity, and outcome in pneumococcal meningitis. We identified adults with culture-proven pneumococcal meningitis in a prospective cohort study (2006–2014). We measured estradiol and testosterone in CSF using liquid chromatography-tandem mass spectrometry and sex hormone-binding globulin (SHBG) using an enzyme-linked immunoassay. Hormone levels were compared according to outcome, which was graded using the Glasgow Outcome Scale (a score of 5 indicating favorable, 1–4 unfavorable outcome). Correlation analysis was used to measure the association between hormone levels and inflammatory cytokines, chemokines, and complement factors as well as severity of illness, as measured by the Glasgow Coma Scale and the Dutch Meningitis Risk Score. We included 60 patients: 20 men, 20 premenopausal (<50 years), and 20 postmenopausal (>50 years) women. Twenty-one (35%) patients had an unfavorable outcome and 11 (18%) died. Cases with an unfavorable outcome exhibited higher estradiol (median 14.0 vs 5.0 pmol/L, P  = .04) and lower SHBG (0.40 vs 1.0 nmol/L, P  = .03) levels compared with those with a favorable outcome. Estradiol was positively correlated with C-reactive protein ( R  = 0.42, P  = .001), CSF protein ( R  = 0.33, P  = .01), and proinflammatory cytokine levels. CSF concentrations of the sex steroid hormone estradiol were associated with outcome and CSF inflammation. Understanding the dose and time-dependent interaction between sex steroid hormones and the inflammatory response in bacterial meningitis represents an important and understudied topic.